Lumbar load in adolescent fast bowlers: A prospective injury study - Bayne, H.; Elliott, B.; Campbell, Amity; Alderson, J. (Elsevier Ltd, 2014)
Objectives: This study aimed to identify modifiable mechanisms associated with low back injury in adolescent cricket fast bowlers. Design: A prospective study design examined the association between intrinsic risk factors, workload, bowling kinematics, lumbar load and low back injury incidence. Methods: Twenty-five injury free fast bowlers, aged 14-19 years, were assessed prior to the start of a cricket season and observed during the season for low back injuries. Results: The twelve bowlers who suffered a low back injury displayed; decreased hip flexion at front foot contact (46±6° vs 51±6°), increased pelvis rotation (287±11° vs 277±11°) increased thorax lateral flexion (50±6° vs 40±8°) at ball release, and larger peak lumbar flexion (10.5±4.9Nmkg-1 m-1 vs 6.9±2.5Nmkg-1 m-1) and lateral flexion moments (12.5±2.6Nmkg-1 m-1 vs 10.6±1.9Nmkg-1 m-1). They also exhibited reduced muscular endurance of the back extensors (103±33s vs 132±33s) and increased knee valgus angle during a single leg decline squat on the dominant (9±3° vs 5±4°) and non-dominant leg (9±4° vs 6±3°) in comparison to uninjured bowlers. Conclusions: Bowlers who experience greater lumbar loads during bowling, have reduced back extensor muscle endurance, and demonstrate impaired control of the lumbo-pelvic-hip complex, are at increased risk of low back injury. This combination of strength, control and biomechanical factors may be key mechanical elements of low back injury causation in adolescent fast bowlers.